Pemberian Edukasi pada Remaja Tentang Teknik Akrupesure untuk Meminimalisir Dismenorea - Salmawati Salmawati; Emi Yunita (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Dysmenorrhea is a common complaint among adolescent girls and can interfere with daily activities and quality of life. One safe and easily applicable non-pharmacological management is acupressure techniques. This community service activity aimed to improve the knowledge and skills of adolescent girls in managing menstrual pain through education and acupressure training. The implementation methods included educational sessions, hands-on practice of acupressure techniques, and evaluation using pre-test and post-test assessments. The results showed an increase in participants’ knowledge and skills after the training. The average knowledge score increased from 56 to 86 after the intervention in Majungan Village, Pademawu District, Pamekasan Regency. In addition, there was a reduction in the intensity of menstrual pain, with a 36% decrease in mild pain and a 20% decrease in moderate pain. A total of 88% of participants were able to correctly identify acupressure points and practice them independently. This activity was proven effective in helping adolescent girls manage dysmenorrhea naturally through acupressure. In conclusion, the program effectively improved the knowledge, skills, and behavior of adolescent girls in managing dysmenorrhea through acupressure.